On the Müller-Lyer Illusion in the Carpentered World. (July 2013) - Deręgowski, Jan B
Implications of the little noticed fact that projective geometry restricts the range of interfin angles of the Müller-Lyer illusion, which are congruent with retinal projections cast by carpentered objects, are presented and tested. Experimental results support the theoretical restrictions. This implies that only Müller-Lyer figures with interfin angles within the 90° to 180° range are appropriate for investigation of the Carpentered World hypothesis.